Biodiversity information systems using georeferencing and physical identification - Tiago Lira (2011)
Biodiversity information can be found in diverse information systems, ranging from large technical repositories for research purposes to dedicated databases supporting the web presence of natural sites. To deal with individual botanical objects, it is important to adopt the established scientific taxonomy. Providing a satisfying experience with current interface devices is also mandatory. Two problems have been addressed in this work: the unique identification of the objects and the representation of their physical location. The former has been tackled with QR code, a two-dimensional barcode standard, and the latter with the use of a PostgreSQL/PostGIS spatial database. The paper describes the development and test of a Web information system integrating physical identification and geo-referencing. The application in biodiversity information management shows that low-cost, state-of-the-art technologies can provide appropriate solutions even for small- and medium-sized natural sites, incorporating existing scientific information on species and contributing for a growing record of their occurrences. The system was tested on a university garden and can be used by site maintainers, visitors and researchers. The dataset collected in the site can be exported according to the Darwin Core biodiversity standard for research purposes.